Safe explantation of spinal cord stimulator paddle electrodes - Zachary T. Olmsted; Michael J. Dorsi (World Neurosurgery: X)
Objectives: Spinal cord stimulation (SCS) technology has become increasingly utilized and understood as a treatment for chronic pain. Epidural paddle electrodes have the advantage of lower rates of migration and infection. While percutaneous leads can be explanted without open surgery, paddle electrode explantation has been considered a high risk procedure. We describe our operative technique and the safety of SCS paddle electrode removal. Methods: Twenty-four consecutive patients underwent SCS paddle stimulator explantation at a single institution between 2017 and 2024. The study was designed to evaluate the safety of SCS paddle electrode removal. Explant patients were identified by CPT code. Cervical explantation patients were excluded from this analysis. We reviewed demographic data, operative technique and postoperative outcomes. We present an operative technique for the safe explantation of paddle electrodes and report on outcomes within 60 days of reoperation. Results: Paddle electrodes were explanted in 24 patients with mean age 59.6 ± 17.4 y (range 25–85). The interval between implant and removal ranged 4–192 mo. Reasons for explantation included ineffective pain relief (n = 16), pain resolution (n = 3), generator pocket pain (n = 4), paddle malpositioning (n = 1), progressive neurologic symptoms related to SCS (n = 3), and need for MRI (n = 7). We emphasize exposing the base of the paddle for ease of removal at the level of insertion. Conclusions: For ineffective pain control or morbidity related to SCS, surgically placed paddle electrodes can be safely and consistently explanted, even after epidural scarring has occurred. Careful exposure of the paddle base is critical. This approach stands in contrast to battery removal only, which is not compatible with future MRI studies.